2018
DOI: 10.1111/pim.12598
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dirofilaria immitis immunoreactive proteins in serodiagnosis

Abstract: Dirofilariasis is a zoonotic global vector-borne disease caused by Dirofilaria immitis.The present study focuses on the somatic and excretory/secretory (E/S) proteins released from adult D. immitis. We aimed to fractionate and identify adult D. immitis immunoreactive proteins. Somatic and E/S extracts were immunoblotted to identify the immunoreactive proteins. In the current study, we used matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF/MS) to characterize the immunogenic proteins. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…To our knowledge, this study represents the first simultaneous identification of immunogenic antigens of D. repens adult worms and microfilariae in serum collected from naturally infected dogs. Molecules that we identified in D. repens tissue extracts have been previously considered a potential diagnostic target, vaccine candidates, and drug targets for treating, e.g., schistosomiasis [33][34][35], cestodiasis [36][37][38][39][40][41][42], and parasitic nematodes [43][44][45][46][47][48][49][50][51][52]. Our analysis also confirmed the existence of molecules for which antigenic properties have never been considered in Dirofilaria genus.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…To our knowledge, this study represents the first simultaneous identification of immunogenic antigens of D. repens adult worms and microfilariae in serum collected from naturally infected dogs. Molecules that we identified in D. repens tissue extracts have been previously considered a potential diagnostic target, vaccine candidates, and drug targets for treating, e.g., schistosomiasis [33][34][35], cestodiasis [36][37][38][39][40][41][42], and parasitic nematodes [43][44][45][46][47][48][49][50][51][52]. Our analysis also confirmed the existence of molecules for which antigenic properties have never been considered in Dirofilaria genus.…”
Section: Discussionsupporting
confidence: 78%
“…Cytoskeleton proteins (actin, tubulin, myosin, and paramyosin) were previously found in D. immitis [51,53,[65][66][67][68]. In the present study, cytoskeleton proteins were identified as potential antigens in both developmental stages (actin).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Apart from using MALDI-TOF MS as a new tool for the identification of adult worms or larvae, other studies focused on the characterization and identification of specific nematode proteins. Khanmohammadi and colleagues [ 30 ] studied the characterization of immunogenic proteins of D. immitis using MALDI-TOF MS. Herein, authors collected adult worms from six infected dogs and cultivated them in cell culture flasks containing roswell park memorial institute (RPMI)-1640 medium and other substances. Afterwards, the medium was submitted to successive steps of centrifugation, filtration, homogenization, and sonication in order to retrieve the in vivo secretome (somatic and excretory/secretory (E/S) protein extracts).…”
Section: Specific Application Of Maldi-tof Ms For Different Helminthsmentioning
confidence: 99%
“…In the initial diagnosis stage, blood smears were stained with Wright and a thick drop stained with Giemsa or Knott´s test for a microscopic examination that allowed us to recruit positive cases. All cases detected by microscopy were also analyzed with a serological test that specifically detects the secreted 14KDa antigen of D. immitis [50] (Canine Heartworm Ag 2.0 Bionote, Inc, Korea).…”
Section: Clinical Laboratory Testingmentioning
confidence: 99%